OPTIMALISASI TIKTOK DAN WHATSAPP BUSINESS: PELATIHAN DIGITAL MARKETING UNTUK TINGKATKAN PENJUALAN PENGRAJIN BATIK DI DESA KLAMPOK - Faruq, Umarul; Subairi, Subairi; Mubarak, Reza; Rachman, Titik Herdiana; Alif, Subhan (PENA DIMAS: Jurnal Pengabdian Masyarakat, 2024)
Klampar Village in Pamekasan Regency has great potential in the batik industry, with the largest proportion of batik makers in the region. Batik making is the main activity and attraction for tourists. The uniqueness of Klampar batik lies in its richness of colors, with more than three colors in one cloth, including dark brown, black, red and green, which makes it superior to other batik centers. Some batik artisans already have their own UD/CV, showing promising economic potential. The village also has stable internet access, which opens up opportunities for effective digital marketing. The objective of this community service activity is to build the capacity of batik artisans in Klampar Village to use TikTok social media and WhatsApp Business to increase sales of their batik products. This community service activity uses the Asset Based Community Development approach with five stages: inculturation, discovery, design, definition, and reflection. The core of this activity is to provide digital marketing training using TikTok and WhatsApp Business to the target community. As a result of this activity, the community has increased their skills in using TikTok and WhatsApp Business applications to market their batik products. They are now able to enter products, create attractive descriptions, manage catalogs, communicate with customers, and conduct transactions using the two applications.